USING THE METHOD OF CINQUAIN IN THE STUDY OF ATTITUDES TO PEOPLE WITH DISABILITIES - Perelygina, I.A. (Modern Psychology, 2019)
The article reveals some regularities of the formation of individual attitude to a person with disabilities in the development of the value concept of inclusion. This research is aimed to studying and changing the personal attitudes of "normal" people towards people with disabilities. The technique of "Cinquain" as a psycho-diagnostic tool is described. The study involved 200 people from 6 to 60 years. The results prove that "Cinquain" can be used as a projective technique that helps to identify the main psychological problems associated with the perception of disability. It is necessary to change stereotypes about people with disabilities from an early age. After all, it is much more difficult to change the consciousness of adults than to instill in the younger generation a tolerant, positive attitude to the disabled in a timely manner. Writing cinquain requires a person to implement almost all of his personal abilities (intellectual, creative, social, communicative). Chinquapin allows you to harmoniously combine the elements of the main educational systems: information, activity, personality-oriented and promotes the search and finding of internal resources.